GERAKAN KOMUNITAS CANGKIR KAMISAN MEMBANGUN EKONOMI KREATIF DI METRO LAMPUNG - Setyawan, Dharma (BISNIS, 2015)
This Research reveals the role of the Community Cup Kamisan.A community that started its operations from discussions talk think(cups) in the core of the house of the host. Anxiety the pegiatnyaconsisting of academics, activists, journalists, citizen, teachers,businessmen, were enterprising, and various creative communitycity. Kamisan Cup community is attempting to revive the role of thevarious entities in the City Metro Lampung with spirit to build thecollective intellectual property. Lampung province which is knownwith various ethnic conflict, through collective intellectual movementis starting to realize the importance of building togetherness. Borrowedthe term Arnold J. Toynbe namely build «creative minority” namely CupsKamisan community efforts to build the city with the empowerment ofvarious community entities.Kamisan Cup community is a multicultural community whoare also trying to develop a creative economy. Consists of variousbackgrounds from academics, Student activists, journalists, creativecitizens, religious leaders unite the idea of building a social movement.Many changes occur from build Citizen journalism portal pojoksamber.com, House Together, research institution Sai Wawai Institute,publication of indie Sai Wawai Publishing, and establish Waste BankGreen cups. In addition many movements of other creative economythat is done by this community. E.g. with began to build the othercreative economy documentary, music, and handicrafts.Intellectual Property and the community experienced abecause it is based on the logic of politics and keilmuwan at the timeof the formation of the term intellectual property. “intellectuals” bornfrom social classes who do claim against the injustice done by the state.The state since the formation, have special characters in the form ofdomination. In the second phase of the state that is free, that dominationcontinues to the community. In this case, researchers intend to explorethe role of the Community Cup Kamisan answer the challenge inbuilding the structure of the output of the community and are ableto progress and work for the community. The collective intellectualdiscourse interesting to examined as part of the responsibility ofuniversities build changes through the way intellectualism naturallydissipate namely knowledge. The meaning of this research is toexamine more in the role of the Community Cup Kamisan in buildingthe creative economy in the City of Metro Lampunng